Evidence-based treatment of Tourette's disorder and chronic tic disorders. (2nd November 2019) - Essoe, Joey Ka-Yee; Grados, Marco A.; Singer, Harvey S.; Myers, Nicholas S.; McGuire, Joseph F.
ABSTRACT: Introduction : Chronic Tic Disorders and Tourette's Disorder (collectively referred to as TD) are characterized by sudden, rapid, and repetitive motor movements or vocalizations called tics. Children, adolescents, and adults with TD often experience co-occurring psychiatric symptoms and impairments in multiple domains. As a result of tics and other symptoms, patients with TD can develop negative self-views, require considerable accommodations, and experience a poor quality of life. Therefore, the efficient and effective management of TD bears considerable importance. Areas covered : This expert review evaluated the empirical support for behavioral and pharmacological interventions based on the results of randomized controlled trials (RCTs). Behavioral interventions evaluated include habit reversal training (HRT), comprehensive behavioral intervention for tics (CBIT), and exposure response prevention (ERP). Reviewed pharmacological interventions included alpha-2 agonists, antipsychotics, and anticonvulsants. Expert opinion : This review identified several efficacious behavioral and pharmacological interventions for TD. However, several gaps in the management of TD include: (1) the access/availability of behavioral interventions, (2) novel and more efficacious treatment approaches, and (3) the development of more comprehensive interventions to manage TD. In order to advance the treatment of TD, additional research is necessary to efficiently, effectively, and comprehensively develop and evaluate new treatments for patients with TD.